Transforaminal epidural steroid injection for recurrent lumbar disc herniation (Annals of Medical Research, 2021)
Aim: Transforaminal epidural steroid injection reduces the low back-leg pain which caused by lumbar disc herniation (LDH). The aim of our study is to evaluate the treatment of transforaminal epidural steroid injection for recurrent LDH. Materials and Methods: 19 patients were included in our study who were treated by transforaminal epidural steroid injection for recurrent LDH in our clinic between 2014 and 2018. We evaluated the patients pre-procedure and at 2 weeks, 3 and 6 months after treatment by Visual Analogue Scale / Oswestry Disability Index (ODI) and followed up for surgical treatment after 6 months.Results: The mean low back and leg pain VAS was 4.2±0.6 before TFESI procedure and it was 1.9±0.3 after two weeks. İt was 2.1±0.3, 3.6±0.8 at 3 and 6 months after procedure respectively. The reduction of low back and leg pain mean VAS is statistically significant between before treatment and at 2 weeks and at 3 months after TFESI procedure respectively (p0.05). The mean ODI was 21.4±0.3 before TFESI procedure and it was 12.4±0.7 after two weeks. İt was 15.3±0.5 and 18.2±0.1 at 3 and 6 months after procedure respectively. The four of all patients were treated by microdiscectomy for recurrent LDH.Conclusion: The transforaminal epidural steroid injection is safely treatment for non-surgical treatment of recurrent LDH. Our study recommends that transforaminal epidural steroid injection should be considered before surgical intervention and this procedure may support to surgical indication of recurrent LDH.
Keywords: Non-surgical treatment; recurrent lumbar disc herniation; transforaminal epidural steroid injection